Inclusion and the ‘Arts of Resistance’: How Do Roma Migrants Develop Autonomy in the Context of Inclusion Policies? - Clavé-Mercier, Alexandra; Olivera, Martin (Intersections. East European Journal of Society and Politics, 2018)
During the last 20 years, processes of social, spatial or economic exclusion suffered by a growing number of people identified as ʻRomaʼ in Europe were progressively investigated and better documented, as, for instance, legal (or para-legal) measures implemented against Roma migrants living in precarious settlements in Western Europe. Over the same period, international or European institutions, national authorities and many NGOs significantly developed local or regional initiatives for ʻRoma inclusionʼ. From ethnographic investigations conducted during several years in two French cities which have implemented social support and housing projects toward Roma immigrants families (Bulgarian in one case, Romanian in the other), this article firstly aims to highlight the effects of the contradictions and paradoxes characterizing the launch and running of many ʻinclusion policiesʼ which, like exclusion policies, are frequently based on stereotypical conceptions of ʻRomaʼ as well as of ʻsocial integrationʼ. Reversing the point of view, we will secondly light the way the ʻtarget familiesʼ of these projects may nevertheless succeed to preserve leeway and to develop different forms of local insertion, using (or not) resources provided by public policies as well as personal and family resources. In so doing, this paper proposes to address the role and value of informality and ʻproductive misunderstandingsʼ in these dynamics of emancipation and effective integration taking place in a strongly binding context.